Sarjana (Sarana Belajar Anak Jalanan): Pemberdayaan Anak Jalanan Mandiri, Kreatif Dan Inovatif Melalui Pendidikan Kewirausahaan - Basam, Fajri; Amal, Amri (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Makassar city is one of the cities in Indonesia that can not be separated from the problem of street children. Street children are a very vulnerable social group from various acts of violence, whether physical, emotional, sexual or social violence. Therefore, through the program of dedication to the community intend to participate actively in solving the problems of street children through the program "SARJANA (Sarana Belajar Anak Jalanan): Empowerment of Independent Street Children, Creative, and Innovative Through Entrepreneurship Education". The expected expenditure of this program is to enable street children to become independent, creative and innovative in that it no longer becomes a begging demanding society through entrepreneurship education and the provision of appropriate skills in a relatively short period of time. Methods of implementation are: (1) providing entrepreneurial materials, (2) Production and Financial Management materials, (3) Marketing Management Materials, (4) motivational materials, (5) monitoring and evaluation. The result of this devotion is that the built children already have the creative ability to produce various products that can be the future to be self-supporting.